2015
DOI: 10.1002/anie.201507524
|View full text |Cite
|
Sign up to set email alerts
|

Microhydration Effects on the Ultrafast Photodynamics of Cytosine: Evidences for a Possible Hydration‐Site Dependence

Abstract: Ultrafast excited-state deactivation dynamics of small cytosine (Cy) and 1-methylcytosine (1mCy) microhydrates, Cy⋅(H2O)1-3 and 1mCy⋅(H2O)1,2, produced in a supersonic expansion have been studied by mass-selected femtosecond pump-probe photoionization spectroscopy at about 267 nm excitation. The seeded supersonic expansion of Ar/H2O gas mixtures allowed an extensive structural relaxation of Cy and 1mCy microhydrates to low-energy isomers. With the aid of electronic structure calculations, we assigned the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
(128 reference statements)
4
13
1
Order By: Relevance
“…With the aid of electronic structure calculations, we assigned the observed ultrafast dynamics to the dominant microhydrate isomers of keto-Cy. Our results indicated that single-water hydration at the sugar-edge site of keto-Cy barely alters the excited-state lifetime (∼0.5 ps), whereas microhydration with two or three water molecules exhibits a marked lifetime shortening to ∼0.2 ps . In this work, we extend our previous studies to explore microsolvation effects on the excited-state deactivation dynamics in larger Cy hydrated clusters with n = 4–6 as well as small Cy clusters with another protic solvent, methanol (MeOH), and with an aprotic solvent, tetrahydrofuran (THF).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…With the aid of electronic structure calculations, we assigned the observed ultrafast dynamics to the dominant microhydrate isomers of keto-Cy. Our results indicated that single-water hydration at the sugar-edge site of keto-Cy barely alters the excited-state lifetime (∼0.5 ps), whereas microhydration with two or three water molecules exhibits a marked lifetime shortening to ∼0.2 ps . In this work, we extend our previous studies to explore microsolvation effects on the excited-state deactivation dynamics in larger Cy hydrated clusters with n = 4–6 as well as small Cy clusters with another protic solvent, methanol (MeOH), and with an aprotic solvent, tetrahydrofuran (THF).…”
Section: Introductionsupporting
confidence: 60%
“…In order to bridge the gap between the gas-phase and aqueous-phase dynamics, we have recently reported a joint experimental and computational study on Cy small microhydrates, Cy·(H 2 O) n , with n = 1–3, to explore the microhydration effects on the excited-state deactivation dynamics of keto-Cy . With the aid of electronic structure calculations, we assigned the observed ultrafast dynamics to the dominant microhydrate isomers of keto-Cy.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by application of various spectroscopic experiments and/or theoretical calculations using explicit water models. [7][8][9][10][11] Hence the organic solvents which are miscible with water are ultimately used for these kind of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…16,18,19 Besides the possible role of deamination processes, 15,20 hotspots containing 5-methylcytosine are up to 5 to 15-fold more sensitive to pyrimidine photodimerization upon ultraviolet irradiation compared to C. [21][22][23] The steady-state and Time-resolved (TR) spectroscopic properties of 5-methylcytosine have been tackled by several studies. [24][25][26][27] From a theoretical point of view, other C derivatives have received more attention [27][28][29][30][31][32][33][34] and the works on 5-methylcytosine are instead scarce and limited to the gas phase. 31,35,36 Eventually, it is also apparent that interaction with the environment (including the solvent as well as the sugar moiety) is mandatory to appreciate and understand all the effects recorded in vivo.…”
Section: Introductionmentioning
confidence: 99%